Pelatihan Trik Pemasaran Dengan Meningkatkan Pendapatan Melalui Media Sosial - Dede Suleman; Imelda Sari; Taat Kuspriyono; Dedi Suharyadi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2021)
This journal contains the results of research related to training in marketing tricks to increase income with the help of social media. In the current marketing program, efforts to increase income need to be carried out apart from offline sales, it also needs to be done with online activities. One of the obstacles could be the lack of knowledge from the company team in using online marketing methods, especially through social media. Currently the company's marketing activities were previously carried out offline through advertising marketing and other print media in the form of distributing brochures or pamphlets and then continuing with marketing through print media and electronic media. Currently, both types of marketing activities are considered ineffective, especially in the midst of the Covid-19 pandemic, which has not yet ended. The main problems experienced by companies today include low income due to the impact of the pandemic where offline marketing activities are experiencing a pandemic so there needs to be a solution for marketing methods with new methods. One solution that is trying to be delivered in this community service activity is training on the use of social media. could be Instagram. So, it can be said that this could be one of the solutions in digital marketing with more emphasis on the use of social media in marketing products to increase company income.